2022
DOI: 10.3390/brainsci12030298
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Repetitive Transcranial Magnetic Stimulation in the Treatment of Bipolar Disorder in Comparison to the Treatment of Unipolar Depression in a Naturalistic Setting

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is effective in the treatment of depression. However, for the subset of patients with bipolar disorder, less data is available and overall strength of evidence is weaker than for its use in unipolar depression. A cohort of 505 patients (of which 46 had a diagnosis of bipolar disorder) with depression who were treated with rTMS were analyzed retrospectively with regards to their response to several weeks of treatment. Hamilton Depression Rating Scale (HDRS) wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Recent publications have demonstrated no difference in the HDRS score between the groups [ 19 ], but they underline an interest in studying the effectiveness of rTMS in a distinctive manner through these two diagnoses [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent publications have demonstrated no difference in the HDRS score between the groups [ 19 ], but they underline an interest in studying the effectiveness of rTMS in a distinctive manner through these two diagnoses [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alhelali et al demonstrated a difference in the effect of rTMS between bipolar and unipolar patients with respect to items 10 and 11 [ 8 ]. Similarly, we observed a difference in the effect of rTMS with respect to the anxiety sub-score while grouping the items together.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic review and meta-analysis of rTMS for Bipolar Depression indicated that it is safe and effective with low-risk side effects ( 24 , 25 ). Furthermore, depressed patients with a diagnosis of BD benefit from rTMS in a similar fashion as patients with unipolar depression in a naturalistic setting ( 26 ).…”
Section: The Evidence For Repetitive Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…Concerning rTMS, Alhelali et al [ 11 ] investigated the effects of rTMS in a large cohort of patients with unipolar and bipolar depression ( n = 505). High-frequency rTMS protocols were applied over the left or right dorsolateral prefrontal cortex or the medial prefrontal cortex (mean number of sessions: 18–19).…”
Section: Clinical Outcomes and Neurostimulationmentioning
confidence: 99%